Associação de diferentes doses de clonidina à bupivacaína no bloqueio peridural caudal para correção cirúrgica de hipospádia em crianças: estudo prospectivo, encoberto e aleatorizado - Ana Claudia Mota Bonisson (2016)
The adequate control of postoperative pain is very important for children care. The assessment and management of pain in children can be complicated by their inability to communicate effectively and therefore it is very difficult to access and classify regarding the severity of their pain. Among the analgesia techniques available, caudal epidural anesthesia is an optional technique and a favorable risk-benefit .Caudal epidural block is one of most popular and safe technique in pediatric analgesia and provides good pain control for a variety of surgical procedures. Several local anesthetics and adjuvant drugs have been studied to improve analgesia quality and reduce side effects. The aim of this study was to investigate the efficacy and safety of the clonidine-bupivacaine association in caudal epidural block for children submitted to hypospadias surgery. On this prospective, randomized and double-blind study, eighty male pediatric patients, ranging from one to ten years-old, were submitted to hypospadias surgery by inhalation anesthesia combined with caudal epidural block .The patients were separated in four groups, that received 1 ml/Kg of four different solutions in the caudal epidural space : 0,166% bupivacaine (B group): 0,166% bupivacaine plus clonidine 1g/Kg (BC1 group) ; 0,166% bupivacaine plus clonidine 2g/Kg ( BC2 group) 0,166% bupivacaine plus clonidine 3g/Kg (BC3 group). The following parameters were evaluated during the surgery: duration of surgery and anesthesia, heart rate (HR), mean blood pressure (MBP), sevoflurane expired fraction and anesthesia wake-up time. During the postoperative period heart rate (HRPO), mean blood pressure (MBPPO), intensity of pain, scores of sedation, morphine consumption, the duration of analgesia and incidence of side effects were evaluated. The behavioral FLACC scale (face, legs, activity, cry and consolability) was used to grade pain. Ramsay score was used to check sedation. During the surgery there was no statistically significant difference among the groups regarding age, weight, HR, MBP and expired fraction of sevoflurane. During the postoperative period there were statistical differences in the BC3 and B groups. The HRPO was slightly lower in group BC3 in comparison to group B at the second and sixth hour after surgery. At BC3 group after 4 ,5, and 6 hours of surgery it was also noted an increase in sedation scores. The pain scores and duration of analgesia, anesthesia wake-up time and side effects were similar between groups. Concluding, caudal epidural block with bupivacaine associated to clonidine at 1, 2 or 3 g/Kg did not provide additional effect on analgesia in comparison with 0,166% bupivacaine in pediatric patients submitted to hypospadias surgery. The patients that used clonide at dose of 3g/Kg presented low levels of HRPO and higher sedation scores.